Effect of Voltage, Current, and Power on revolutions per minute in the brushless direct 3000-Watt current motor on E-Gokart - Iqbal Imaduddin; Doni Fajar Ramadhan; Ridwan Adam Muhamad Noor (Universitas Pendidikan Indonesia (UPI), 2021)
The internal combustion engine is a gasoline-powered internal combustion engine that is widely used in the world of transportation. Therefore, everyone is starting to think about developing alternative fuels that are fuel efficient, easy to upgrade, and better in terms of emissions. Vehicles with electric motors are one of the right solutions because they are more environmentally friendly and do not cause pollution when used. In this study, we will discuss the performance of the brushless DC electric motor that is applied to the Go-kart based on the voltage, current, and electrical power that occurs. The method used is measurement using software and experimental simulations. Based on the test results using Votol_V3 Voltage, current, power, and rotation per minute (rpm) have a relationship, the higher the rpm on the mid-drive type electric motor, the greater the current and power required.